The Implementation of Chemical Castration Penalties towards Paedophilia Crime Perpetrators - Kartono Kartono; Aji Mulyana (Universitas Lampung, 2019)
Sexual crime (rape) is one of the crimes that are very disturbing to the community, and its development is increasingly diverse either in the motives, nature, the form, the intensity and the modus operandi. The concerning situation is that a castration or castration law is expected to encouraging perpetrators of child sexual violence to lose their desire to repeat their crime. This research will explain how the implementation of chemical castration against sexual offenders on children (paedophilia) and how the application of castration penalties after the purpose of Indonesian crimes. The implementation of the imposition of the chemical castration sentence seems to be considered as an answer to the high public demand for severe punishment for the perpetrators. The existing rules of criminal law and child protection have never been implemented optimally. The Act of sexual assault on a child brings harmful impacts against physical and psychology to the victim, which became an obstacle for law enforcement officers to know or detect victims of sexual violence against children.